Increase of RT-Related Transmitted Drug Resistance in Non-CRF01_AE Among HIV Type 1–Infected Men Who Have Sex With Men in the 7 Cities of China. (1st March 2015) - Zhao, Bin; Han, Xiaoxu; Xu, Junjie; Hu, Qinghai; Chu, Zhenxing; Zhang, Jing; Lu, Lin; Wang, Zhe; Fu, Jihua; Chen, Xi; Yan, Hongjing; Zhuang, Minghua; et al.
Abstract : Objectives: To elucidate new features in the prevalence of HIV-1 transmitted drug resistance (TDR) in men who have sex with men (MSM) in China. Methods: A total of 441 HIV-1–positive subjects were recruited from high-risk MSM populations in 7 cities across China between 2012 and 2013. Nucleotide sequences of 1.1-kb pol -RT regions were amplified and sequenced from 367 of the 441 samples. Phylogenetic and genetic drug-resistant analyses were performed. Results: The overall distribution of HIV-1 genotypes was as the following: CRF01_AE, 52.3%; CRF07_BC, 33.2%; 01/B recombinants, 6.0%; subtype B (United States–European), 3.8%; subtype B′, 3.8%; and CRF08_BC, 0.8%. About 91.3% of the sequences clustered together. An overall 4.6% TDR rate was found. Reverse transcriptase (RT)-related TDR reached 2.7%. TDR of 2.2% was detected in protease region. Most of RT-related TDRs were detected in non-CRF01_AE subtypes (90.0%, 9/10), including T215A/S, K101E, K103N, V106M, and E138G. Most of the strains with TDRs (88.2%, 15/17) were presented in the clusters. TDR strains against non-nucleoside reverse transcriptase inhibitors in non-CRF01_AE subtypes also formed some subclusters (70.0%, 7/10). One CRF07_BC subject with K103N in Kunming had a very close genetic distance with one that received highly active antiretroviral therapy locally (bootstrap = 99%). Two CRF55_01B subjects carrying K103N in Changsha and Nanjing also had a very close genetic distance (bootstrap = 100%). Conclusions: RT-related TDR of non-CRF01_AE became the main TDR among MSM in China. There is an increasing trend and a potential transmission risk for the RT-related TDR among MSM throughout China. Some TDRs could have already been transmitted among different cities. Intervention efforts should be strengthened among MSM to prevent further transmission of HIV and the proliferation of the strains with TDR.